Electrophysiological Characteristics of the Migraine Brain: Current Knowledge and Perspectives - Marucco, Erica; Lisicki, Marco; Magis, Delphine (Current Medicinal Chemistry, 2019)
Background: Despite pain being its most prominent feature, migraine is primarily a disorder of sensory processing. Electrophysiology-based research in the field has consistently developed over the last fifty years. Objective: To summarize the current knowledge on the electrophysiological characteristics of the migraine brain, and discuss perspectives. Methods: We critically reviewed the literature on the topic to present and discuss articles selected on the basis of their significance and/or novelty. Results: Physiologic fluctuations within time, between-subject differences, and methodological issues account as major limitations of electrophysiological research in migraine. Nonetheless, several abnormalities revealed through different approaches have been described in the literature. Altogether, these results are compatible with an abnormal state of sensory processing. Perspectives: The greatest contribution of electrophysiological testing in the future will most probably be the characterization of sub-groups of migraine patients sharing specific electrophysiological traits. This should serve as strategy towards personalized migraine treatment. Incorporation of novel methods of analysis would be worthwhile.
Keywords: electrophysiology